Offshore tax evasion and wealth inequality: Evidence from a tax amnesty in the Netherlands - Wouter Leenders; Arjan Marcel Lejour; Simon Rabaté; Maarten van't Riet (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Exploiting unique datasets covering over 28,000 tax evaders in the Netherlands, we investigate the distribution of tax evasion and its implications for the measurement of wealth inequality. In contrast to Alstadsæter, Johannesen and Zucman (2019), the correction for offshore wealth has only a modest effect on top wealth shares. We show that the distributional pattern of tax evasion depends on the type of tax evasion, e.g. it depends on the offshore country of choice. We explore a number of explanations to account for the differences in results and caution against projecting distributional patterns of detected tax evasion onto still undetected evasion. We also study the dynamic compliance behaviour of tax amnesty participants and document large and sustained increases in reported wealth of around 60% following amnesty participation.Combined with evidence of only a modest increase in the adoption of tax avoidance strategies, this suggests that amnesty participation can lead to substantial public revenue gains.
Keywords: H26; H87; E21; 330; Inequality; Wealth; Tax evasion; Netherlands